Bleeding complications from the direct oral anticoagulants. Issue 1 (December 2015) - Sholzberg, Michelle; Pavenski, Katerina; Shehata, Nadine; Cserti-Gazdewich, Christine; Lin, Yulia
Abstract Background Direct oral anticoagulants (DOACs) are now standard of care for the management of thromboembolic risk. A prevalent issue of concern is how to manage direct oral anticoagulant (DOAC)-associated bleeding for which there is no specific antidote available for clinical use. We conducted a retrospective case series to describe the Toronto, Canada multicenter experience with bleeding from dabigatran or rivaroxaban. Methods Retrospective chart review of DOAC bleeding necessitating referral to hematology and/or transfusion medicine services at five large University of Toronto affiliated academic hospitals from January 2011 to December 2013. Results Twenty-six patients with DOAC bleeding were reviewed; 42 % bleeds intracranial and 50 %, gastrointestinal. All patients had at least one risk factor associated with DOAC bleeding reported in previous studies. Inconsistent bleed management strategies were evident. Median length of hospital stay was 11 days (1–90). Five thromboembolic events occurred after transfusion based-hemostatic therapy and there were six deaths. Conclusions Management of DOAC bleeding is variable. Clinical trial data regarding DOAC reversal is needed to facilitate optimization and standardization of bleeding treatment algorithms.